2020
DOI: 10.1038/s41598-020-75105-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI using relaxometry in malignant gliomas detects contrast enhancement in peritumoral oedema

Abstract: Malignant gliomas are primary brain tumours with an infiltrative growth pattern, often with contrast enhancement on magnetic resonance imaging (MRI). However, it is well known that tumour infiltration extends beyond the visible contrast enhancement. The aim of this study was to investigate if there is contrast enhancement not detected visually in the peritumoral oedema of malignant gliomas by using relaxometry with synthetic MRI. 25 patients who had brain tumours with a radiological appearance of malignant gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…An interesting study by Blystad et al (2020) analyzed peritumoral edema of malignant gliomas using quantitative analysis of T1 and T2 mapping sequences, concluding that mapping techniques may be suitable for identifying peritumoral infiltrative growth. These results are in line with other interesting observations made by using mapping techniques in analyzing the peritumoral zones of high-grade gliomas [8].…”
supporting
confidence: 92%
“…An interesting study by Blystad et al (2020) analyzed peritumoral edema of malignant gliomas using quantitative analysis of T1 and T2 mapping sequences, concluding that mapping techniques may be suitable for identifying peritumoral infiltrative growth. These results are in line with other interesting observations made by using mapping techniques in analyzing the peritumoral zones of high-grade gliomas [8].…”
supporting
confidence: 92%
“…Although the microscopic tumor contents of the PTR is not appreciated with standard MRI sequences, several groups have attempted identifying areas of microscopic disease using sequences like DWI, dynamic susceptibility-weighted contrast-enhanced perfusion imaging (DSC), diffusion tensor imaging (DTI), magnetic resonance spectroscopy, and relaxometry [5,[14][15][16]. While several studies have correlated the MRI ndings with targeted tissue specimens with reasonable radiology-histology agreement, temporal correlation with speci c areas of tumor progression has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional MRI offers only anatomical and morphological characteristic through visual comparison, which cannot obtain quantitative information. Synthetic MRI which is not affected by the scanner settings, inhomogeneity of the B1-eld and coil sensitivity pro le provided with additional quantitive information about gliomas grading [14]. We retrospectively explored the diagnostic performance of synthetic MRI in evaluating gliomas grading and tumor proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies revealed that synthetic MRI with the method of measuring quantitively T1 values of before and after contrast enhancement contributed to detect the enhancement of peritumoral edema which re ected tumor proliferative activity. The enhancement was not usually visible on conventional MRI [14,15]. However, the prediction of gliomas grade and tumor proliferation by synthetic MRI has not been reported.…”
Section: Introductionmentioning
confidence: 91%